1999
DOI: 10.1086/312287
|View full text |Cite
|
Sign up to set email alerts
|

Dark Matter Substructure within Galactic Halos

Abstract: We use numerical simulations to examine the substructure within galactic and cluster mass halos that form within a hierarchical universe. Clusters are easily reproduced with a steep mass spectrum of thousands of substructure clumps that closely matches the observations. However, the survival of dark matter substructure also occurs on galactic scales, leading to the remarkable result that galaxy halos appear as scaled versions of galaxy clusters. The model predicts that the virialized extent of the Milky Way's … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

98
3,104
13
5

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 2,909 publications
(3,220 citation statements)
references
References 37 publications
(53 reference statements)
98
3,104
13
5
Order By: Relevance
“…ρ(r) ∼ r −α int , where α int is close to unity. To this respect a number of discrepancies have been found α int < 1 (e.g., Subramanian et al, 2000;Taylor and Navarro, 2001;Ricotti, 2003), and α int = 1.5 (e.g., Fukushige andMakino, 1997, 2001;Moore et al, 1998Moore et al, , 1999. On the other hand, Hayashi et al (2004); Navarro et al (2004);Power et al (2003), concluded, by using a suite of high resolution simulations, that α int = 1 remains consistent with simulated halo shapes (they found mean values α int = [1.1;1.2;1.35] respectively), while they claim that cusps as steep as α int = 1.5 are ruled out (Spekkens et al, 2005).…”
Section: The Cusp/core Problemmentioning
confidence: 99%
“…ρ(r) ∼ r −α int , where α int is close to unity. To this respect a number of discrepancies have been found α int < 1 (e.g., Subramanian et al, 2000;Taylor and Navarro, 2001;Ricotti, 2003), and α int = 1.5 (e.g., Fukushige andMakino, 1997, 2001;Moore et al, 1998Moore et al, , 1999. On the other hand, Hayashi et al (2004); Navarro et al (2004);Power et al (2003), concluded, by using a suite of high resolution simulations, that α int = 1 remains consistent with simulated halo shapes (they found mean values α int = [1.1;1.2;1.35] respectively), while they claim that cusps as steep as α int = 1.5 are ruled out (Spekkens et al, 2005).…”
Section: The Cusp/core Problemmentioning
confidence: 99%
“…Moore et al (1999) argue that the number of dark matter subhalos is 10 − 100 times larger than the number of satellites observed around the Milky Way (Kravtsov 2010). The so-called "missing satellite problem" has been revisited in a somewhat quantitative context (Boylan-Kolchin et al 2011;Lovell et al 2012;Boylan-Kolchin et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Alternative DM scenarios have been proposed in response to the discrepancy between observations and CDM numerical simulations on small scales (which notably predict cuspy haloes [6]). The most "robust" one, the Warm Dark Matter scenario (WDM), involves non-annihilating particles and a very narrow range for the DM mass [7], obtained by requiring that the freestreaming length be of the order of the smallest primordial scale one wants to be compatible with.…”
Section: Introductionmentioning
confidence: 99%